Interaction of Muslim with Non Muslim (Portrait of Conflict and Its Resolution with Jews of Bani Nadhir) | تعامل المسلم مع غير المسلم (صورة الصراع وحله مع يهود بني النضير) - Sahabuddin, Sahabuddin; Wibowo, Waskito; Hamood, Faisal (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
The topic of interfaith relations has become a global discourse and has attracted the attention of many academics, especially regarding the relationship between Muslims and non-Muslims, specifically Jews in this study. Judaism has a long history with Muslims. The fluctuations in relations between the two parties have continued to occur, reaching their peak in the possession of land in Palestine in this modern era. The purpose of this study is to determine the image of Islamic relations in dealing with Jews based on the books of Sahih al-Bukhari and Sahih Muslim, as well as their contemporary context. The method used for data collection is the library research method. The data analysis technique employed in this study involved descriptive, analytical, and inductive approaches. The research findings indicate that there are 47 hadith topics in the Sahihayn that mention the words